PENGARUH SKALA USAHA UMUR PERUSAHAAN DAN KOMPLEKSITAS TUGAS PENGELOLA UMKM TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Noor Salim; Kiswoyo Kiswoyo (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
The purpose of this study was to determine the effect of business scale, age of the company, and the complexity of the task of managing Micro, Small and Medium Enterprises on the use of accounting information systems. This research was conducted on the manager of Micro, Small and Medium Enterprises furniture in Jepara Regency. Samples were obtained as many as 100 respondents. Methods of data collection using a questionnaire. The data analysis technique used multiple regression analysis with the help of the SPSS program. The results of the study show that (1) Business scale has a positive effect on the use of accounting information systems. (2) Company age has no effect on the use of accounting information systems. (3) The complexity of the tasks of MSME managers has a positive effect on the use of accounting information systems.